Speaking Activities to Improve a Grammatical Aspect and Oral Production in English as a Second Language Students (2020)
In the Pedagogy Concentration of the Languages and Cultures program at Universidad de Los Andes, students must complete a research project or a Pedagogical Practice as one of the requirements to graduate from the program. Thus, the second option was chosen, so the Pedagogical Practice was carried out Instituto Colombiano de Bienestar Familiar (ICBF), teaching English to members of the ICBF. In this context, the practitioner conducted a Participant Observation during the English classes, to find problematic aspects in the learning process of the students, to find solutions to such situations. So, during the observations made by the practitioner, several problematic aspects were found, and the focus was on a grammatical aspect that was problematic, and that also had a negative influence on the students' speaking ability. Consequently, in order to solve this aspect, were proposed series of group activities with a communicative approach and using the "Task-Based Learning" methodology. Finally, it was evidenced an improvement of the students regarding this grammatical issue after having applied the proposed solutions, and it was also observed an improvement in the oral production of the learners.